Rangsangan Warna Cahaya terhadap Prosentase Karkas Ayam Kampung Super - Idrus Umar (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The purpose of the study was to determine the effect of giving different colors of light on carcass percentage and carcass weight in Kampung Super chickens. The research design used was a completely randomized design (CRD). A total of 80 Kampung Super chickens were used in this study. The research treatments were P1 (white light color), P2 (yellow light color), P3 (green light color), P4 (red light color), P5 (blue light color). The results of the study of the highest carcass presentation were found in the treatment that was given red light with an average value of 62.455%. The highest carcass weight was found in the same treatment, which was given a red light with an average value of 674.75 g/head. The provision of different light colors did not have a significant effect on the carcass percentage and carcass weight of the finisher phase super free-range chicken.